SPEECH THERAPY TO PROMOTE ENGLISH FOR AUTISTIC STUDENTS (AN ACTION RESEARCH IN SMP SUNAN MURIA, KUDUS) - Farid Noor Romadlon (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
The opportunity to learn English should be given to all learners since English has been widely spread globally. Learners should be exposed to English as early as possible and be prevalent for all, includingdisabledstudents. Students who need special treatment in learning should also get equal opportunity to study, especially English.One type of disabled students who need special attention in English learning is those who suffer from autism. Autistic students are in need of special treatment learningEnglish since they have more difficulties in perceiving and producing language code. Therefore, English teachers should have awareness on the characteristics of autistic students in terms speech difficulties. In fact, it is highly necessary for autistic students to have intensive therapy and in other sides they also have a right to learn foreign languages like English.Speech therapy as one of therapies used to assist the autistic students in producing language codes is potentially in line with English learning. In this case speech therapy can be done while teaching English to autistic students because speech therapy in fact often requires graded language teaching.   This study focuses on how speech therapy is integrated with English teachingfor autistic students in Second Grader of Junior High School students so as to improve their English proficiency and speech competence as well. The study is an ongoing classroom action research conducted in SMP Sunan Muria in Kudus Regence, Central Java, Indonesia.